Assessment of two novel methods for detecting non-cavitated, smooth surface enamel lesions: an in vitro study - Joel M. White; Pragati Nahar; Puja Kukreti; Jonathan Mangum; Ann Solterbeck; Rachel Jensen; Leslie Plack; Ram Vaderhobli; Larry Jenson (BMC Oral Health)
Abstract Background The objective of this study was to compare two new non-cavitated caries lesion detector methods, LumiCare (LC) and BlueCheck (BC), to each other and to the traditional visual/tactile method (TM) of non-cavitated enamel caries lesion detection on smooth surface lesions. Methods In this non-inferiority study, forty extracted human teeth with International Caries Detection and Assessment System (ICDAS) level 1 and 2 smooth-surface lesions were evaluated in standard operatory conditions by three ICDAS-trained dentists using the traditional visual and tactile method, the LumiCare method, and the BlueCheck method of detection. For each endpoint of Sensitivity (Se) and Specificity (Sp), a generalized mixed model was fitted with positive (negative) agreement (yes/no) as the outcome and method (LC or BC), evaluator and evaluator *method included as fixed effects. Results Statistical analysis shows that the LumiCare and BlueCheck methods of detection are substantially equivalent and compare favorably to the traditional method of lesion detection. Inter-rater reliability and intra-rater reliability ratings were moderate to good. Conclusions This study supports the indications for use for both LumiCare and BlueCheck as aids to visualization of early carious lesions. LumiCare and BlueCheck are substantially equivalent to each other in their ability to differentiate between demineralized enamel and sound enamel. Each may help to educate patients, monitor lesion progression following re-mineralizing therapy, and train beginning dentists in the use of ICDAS.